Efficient partial-denitrification/anammox (PD/A) process through gas-mixing strategy: System evaluation and microbial analysis. (March 2020) - Du, Rui; Cao, Shenbin; Li, Xiangchen; Wang, Jincheng; Peng, Yongzhen
Highlights: High-efficiency continuous PD/A process was achieved by a novel gas mixing strategy. Excellent effluent quality was obtained with short HRT of 0.5 h at temperature of 11.2 °C. Gas mixing significantly promoted nitrite production and anammox activities of PD/A. Sludge floatation was avoided due to enhanced mass transfer and key EPS secretion. Functional bacteria enrichment in PD/A granules was demonstrated under gas mixing. Abstract: Partial denitrification (PD, NO3 − -N → NO2 − -N) provides a promising opportunity for anammox application in wastewater nitrogen removal. In this study, a continuous-flow PD/Anammox (PD/A) process operated with a novel gas mixing was reported in an up-flow anaerobic bed reactor. A high nitrogen removal rate of 2.42 kgN/(m 3 ∙d) was achieved at a relatively short hydraulic retention time (HRT) of 0.5 h with both influent NH4 + -N and NO3 − -N of 30 mg/L. Sludge floatation was eliminated by mixing with gas of the reactor due to an efficiently improved mass transfer. Further optimization of gas flowrates at high NLR could avoid the overproduction of tight-bound extracellular polymeric substances (TB-EPS) and benefit sludge stability. Functional microorganisms of PD and anammox were effectively retained, and Zoogloea affecting sludge settleability kept increasing throughout the operation. This study clearly demonstrated the effectiveness of gas mixing strategy for a high-rate continuous-flow PD/A process with stable nitrogen removal performance.